Body composition of adults with a history of severe acute malnutrition during childhood using the deuterium dilution method in eastern DR Congo: the Lwiro Cohort Study. Issue 6 (28th September 2021) - Mwene-Batu, Pacifique; Wells, Jonathan; Maheshe, Ghislain; Hermans, Michel P; Kalumuna, Esther; Ngaboyeka, Gaylord; Chimanuka, Christine; Owino, Victor O; Macq, Jean; Lukula, Melissa; Dramaix, Michelle; Donnen, Philippe; et al.
ABSTRACT: Background: Few studies have evaluated the body composition (BC) of adults who suffered from severe acute malnutrition (SAM) during childhood, a population at risk of long-term noncommunicable diseases. Objective: We performed an observational cohort study to evaluate BC in a group of young adults aged 11–30 y after nutritional rehabilitation for SAM, in the Democratic Republic of the Congo (DRC). Methods: We evaluated 151 adults in eastern DRC who were treated for SAM during childhood between 1988 and 2007. They were compared with 120 aged- and sex-matched control adults living in the same community who had not been exposed to malnutrition as children. The main variables of interest were the different compartments of adult BC (fat-free mass [FFM], fat mass [FM], and 2 indices of height-normalized BC: FFM index [FFMI] and FM index [FMI]) measured by deuterium dilution. Results: The mean age in both groups was 23 y, and females represented 49% and 56% of the exposed and nonexposed groups, respectively. SAM-exposed males had lower mean ± SD weight (53.6 ± 6.4 compared with 56.4 ± 7.9 kg, P  = 0.029) and lower height (159.9 ± 6.6 compared with 163.6 ± 6.7 cm, P  = 0.003) compared to unexposed males. SAM-exposed subjects had less FFM (–1.56 kg [–2.93, –0.20]; P  = 0.024) but this observation was more marked in males (45.4 ± 5.4 compared with 48.2 ± 6.9 kg, P  = 0.01) than in females. No differences in FM were noted between SAM-exposed and unexposed subjects. Adjusting for height, FFMI and FMI showed no difference between SAM-exposed and unexposed in either sex. Conclusion: SAM during childhood is associated with reduced FFM in adulthood which is probably due to a shorter height.